A comparison of corn fiber gum, hydrophobically modified starch, gum arabic and soybean soluble polysaccharide: Interfacial dynamics, viscoelastic response at oil/water interfaces and emulsion stabilization mechanisms. (September 2017) - Jin, Qiangwei; Li, Xiaobei; Cai, Zhixiang; Zhang, Fei; Yadav, Madhav P.; Zhang, Hongbin
Abstract: The interfacial rheology of polysaccharide adsorption layers of corn fiber gum (CFG), octenyl succinate anhydride-modified starch (OSA-s), gum arabic (GA) and soybean soluble polysaccharides (SSPS) at the oil/water interface and their emulsifying properties in oil-in-water (O/W) emulsions were compared. All four amphiphilic polymers contain different amounts of protein and they are of high molecular weight with highly branched structure. Based on the obtained interfacial shear rheological information such as a number of influence factor dependence (time, concentration, temperature, strain dependency) of interfacial dynamic moduli, creep or relaxation response, and steady/dynamic flow behavior of the interfacial layers, we found pronounced differences in the viscoelastic response of the four hybrid polyelectrolytes in shear flow. The adsorbed film of CFG is unique because it exhibits a predominantly viscous showing an apparently increasing storage modulus throughout the whole test without a saturated value whereas OSA-s produces a pure viscous layer at interface with a very low viscosity and quick forming kinetics; in contrast, both GA and SSPS form more rigid, solid–like layers. Models to describe the distinct interfacial dynamics and stabilizing mechanism of the four emulsifiers involving steric repulsion and electrostatic repulsion are proposed. Emulsifying properties of the four polymers are evaluated in terms of the emulsion physical properties, droplet-size distribution and optical microscopy observation. The effect of concentration and storage temperature on the interfacial viscoelastic response and the corresponding emulsion stability of each biopolymer are also compared. Graphical abstract: Highlights: The interfacial rheology of four high Mw branched polymer emulsifiers is compared. Distinct dynamics and viscoelastic responses are revealed at O/W interface. CFG adsorbed layer is predominantly viscous while OSA-s layer is pure viscous. Elastic layers of GA and SSPS show shear-thinning and yielding behavior. Interfacial dynamics and stability mechanisms are discussed.